THE IMPACT OF SPIRITUAL INTELLIGENCE ON WORK-LIFE BALANCE OF SERVICE SECTOR EMPLOYEES - et. al., Shweta Singh (International Journal of Modern Agriculture, 2021)
In the ever-increasing cut-throat competition, where working long hours and under duress is catching up to be the norm, propagation of work-life balance is being done extensively by companies over past few decades. Companies have sensed that with growing responsibilities, the stress levels also increase and hence different ways of maintaining a healthy work life balance are often introduced. Spiritual intelligence (SI) is a growing buzzword known for reaching higher level of consciousness. The aim of this study is to identify the relationship between the constructs of spiritual intelligence and work life balance (WLB) of professionals among the services sector. A representation framework to understand impact of the four constructs of SI have a relationship with WLB and draw implications of the result to a workplace. The survey consisted a questionnaire based on SISRI for measuring SI is used to validate the model and 222 professionals who worked in different service sectors filled the survey. The findings of analyses for all the stated hypotheses is supported. The findings suggest that all four constructs of SI have a relationship with work-life balance of the working professionals in service sector. Spirituality is growing to becoming an essential indicator in work-life balance, this result is concluded from the study and Spiritual intelligence leads to higher rates of managing work and personal life among employees in this sector and hence it can be used in policy planning and further research in human resource management in organizations